2020
DOI: 10.1002/adma.201908127
|View full text |Cite
|
Sign up to set email alerts
|

A Rechargeable Zn–Air Battery with High Energy Efficiency and Long Life Enabled by a Highly Water‐Retentive Gel Electrolyte with Reaction Modifier

Abstract: Tremendous effort have recently been made in optimizing the air catalysts of flexible zinc–air batteries (ZABs). Unfortunately, the bottleneck factors in electrolytes that largely limit the working life and energy efficiency of ZABs have long been relatively neglected. Herein, an alkaline gel polymer electrolyte (GPE) is fabricated through multiple crosslinking reactions among poly(vinyl alcohol) (PVA), poly(acrylic acid), and graphene oxide followed by intense uptake of an alkali and the KI reaction modifier.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
205
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 210 publications
(207 citation statements)
references
References 92 publications
1
205
0
1
Order By: Relevance
“…Notably, the zinc-air battery with the PBE membrane showed the electrochemical rechargeability over 2500 min (at 20 mAcm −2 and 10 min cycle period), compared to the cell with the Celgard3501 (900 min). Song et al [151] fabricated a PVA, PAA, and graphene oxide (GO) co-crosslinked alkaline GPE, named PVAA-GO. Their approach is a holistic one toward the design of a ZAB.…”
Section: Zn-airmentioning
confidence: 99%
“…Notably, the zinc-air battery with the PBE membrane showed the electrochemical rechargeability over 2500 min (at 20 mAcm −2 and 10 min cycle period), compared to the cell with the Celgard3501 (900 min). Song et al [151] fabricated a PVA, PAA, and graphene oxide (GO) co-crosslinked alkaline GPE, named PVAA-GO. Their approach is a holistic one toward the design of a ZAB.…”
Section: Zn-airmentioning
confidence: 99%
“…Zhang et al 86 functionalized the nanocellulose/GO membrane with quaternary ammonium groups and achieved higher ionic conductivity (i.e., hydroxide conductivity is 58.8 mS/cm at 70°C) (Figure 6A). Song et al 87 reported a PVA, PAA, and GO co‐cross‐linked alkaline gel polymer electrolyte containing the KI additive (Figure 6B). The introduction of GO decreased the crystallinity of PVA and the hydrogel connected through PVAA−GO network was more advantageous in water retention and alkali uptake.…”
Section: Go‐based Solid‐state Electrolytesmentioning
confidence: 99%
“…[132] Present studies focus on addressing these issues to improve the battery lifetime by utilizing novel electrolyte systems. As for the polymer electrolyte materials, various approaches have been proposed including modification of polymer matrices, [133][134][135][136][137] utilization of electrolyte additives, [138,139] exploration of novel ion-conductors, [140] tuning the electrolyte alkalinity, [141,142] and using a carbon dioxide tolerant anion exchange membrane, [143] etc. Excitingly, a crosslinked PVA-PAA-based GPE accompanied with graphene oxide and KI was proposed for flexible ZnÀ air battery, in which the introduced reaction modifier I À could change the conventional path of OER and GO prolonged the diffusion distance to release water from the polymer matrix.…”
Section: Metalà Air Batteriesmentioning
confidence: 99%
“…Excitingly, a crosslinked PVA-PAA-based GPE accompanied with graphene oxide and KI was proposed for flexible ZnÀ air battery, in which the introduced reaction modifier I À could change the conventional path of OER and GO prolonged the diffusion distance to release water from the polymer matrix. The resultant battery showed an exceptionally low charge potential of 1.69 V with a long cycling time of 200 h. [137] Although the obtained cycle life of flexible metalÀ air batteries still falls far behind the requirement in practical applications, every effort reaps the rewards to reach the target of daily use. Besides, the encapsulation of flexible metalÀ air batteries shows promising potential to tackle the challenges of their half-open architectures.…”
Section: Metalà Air Batteriesmentioning
confidence: 99%